Legal Aspects of the plan to Rehabilitation of Insurance Companies Under Interim Administration: A Comparative Study - Alan Bahaddin Abdulla; Bnar Kareem Wasman (QALAAI ZANIST JOURNAL, 2024)
Insurance companies may be exhibit during the exercise of their activity to financial or administrative default, or insurance companies may contravene in the course of performing their activity legal rules settled to preserve the company's entity, the integrity of its transactions and conserve the rights of its customers, and when, for one reason or another, insurance companies are incapable to address their financial difficulties or administrative problems that menace their survival, the regulatory authorities interfere to correct the course of the company with the aim of its survival as a legal entity and to preserve the rights of its customers. One of the most prominent forms of this intervention is the dissolution of the board of directors of the company and the appointment of an interim director of the company, in order to describe the causes of the confusion suffered by the insurance company under temporary management, and to try to countermeasure these disorders by taking a set of financial, legal or administrative means and mechanisms commensurate with the size of the company distressed and the seriousness of its status, under the supervision of the competent authority regulating the insurance sector, to enable the troubled or violating insurance company to overcome its complication in accordance with the plan prepared for this: In light of this, this research was divided into three demands, the first of which was devoted to the intent of the Interim Administration and the rehabilitation process, in the second demand we dealt with the preparation of the rehabilitation plan, and the third and last demand, which we allocated to the vote and approval of the rehabilitation plan. The comparative approach was also relied upon by comparing the position of the Iraqi legal with the (UAE law) and at the end of the research we achieved that the Iraqi legislator's keenness to give the interim director broad discretion to choose the most appropriate way to deal with the difficulties facing the company by negotiating and consulting with creditors. One of the most prominent recommendations we made was the need to amend the (Iraqi Insurance Business Regulation Law), especially the legal texts regulating the rehabilitation of insurance companies under temporary management in a way that ensures the success of rehabilitation procedures in correcting the company's conditions and avoiding bankruptcy or liquidation.